A scoping review of workplace wellness audit tools assessing physical activity and sedentary behaviour. (29th April 2021) - Loitz, Christina C.; Gorman, Erin; Macridis, Soultana; Vaska, Marcus
Abstract: Background: Regular physical inactivity and excessive sedentary behaviour are public and population health concerns. The workplace is an ideal health promotion intervention setting to support employees, particularly office workers. Workplace assessments are a critical component of workplace health promotion programming. The aim of this project was to conduct a scoping review to systematically identify and describe workplace audit tools that assess physical activity and sedentary behaviour influences, as two independent behaviours, through a social ecological lens. Methods: Fourteen electronic databases were searched for academic literature and 69 web‐based resources were searched for grey literature in May 2017. English language workplace audit tools with items on physical activity or sedentary behaviour established in western countries were included. Key characteristics (ie, aim, type, health behaviour, validity, reliability and theory/model/framework) of the audit tools, checklists or questionnaires for office‐based workplaces were identified, described and summarised. Results: The scoping review identified 21 relevant tools. Most tools focused on physical activity alone and did not address sedentary behaviour as a distinct behaviour. Few tools included items assessing physical activity and sedentary behaviour influences across multiple levels of the social ecological model. The most common social ecological focuses in the tools were policy and environmental influences. Conclusions: Numerous workplace physical activity and/or sedentary behaviour audit tools were available. However, a gap was identified as tools and resources that assess and support organisational changes to influence physical activity and sedentary behaviour as two independent health behaviours across multiple social ecological levels within the workplace had not been developed.